2021
DOI: 10.37992/2021.1202.057
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path coefficient analysis for yield, yield components and quality traits in wheat

Abstract: The experiment was conducted during Rabi 2016-17 in randomized complete block design with three replications. Correlation and path analysis was performed for 19 traits of wheat. Grain yield/plant showed a significant positive correlation with the biological yield/plant, plant height, hectolitre weight, harvest index and thousand-grain weight. In path analysis, grain yield/plant exhibited the highest positive direct effect via biological yield/ plant followed by harvest index, whereas wet gluten per cent exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Classical breeding methods, including the selection and release of elite cultivars, as well as the recognition of the agronomic traits as the suitable criteria to use in breeding programs, are being remembered as fast, easy and reliable methods to introduce superior fennel cultivars. Screening the best indicators to use in essential oil yield (EOY%) improvement plans and finding the correlation between EOY% and its components is the first priority [11][12][13]. Piccaglia and Marotti [14] reported that biomass weight and the number of umbels per plant are positively related to the essential oil content (R = 0.651 and 0.569, respectively) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Classical breeding methods, including the selection and release of elite cultivars, as well as the recognition of the agronomic traits as the suitable criteria to use in breeding programs, are being remembered as fast, easy and reliable methods to introduce superior fennel cultivars. Screening the best indicators to use in essential oil yield (EOY%) improvement plans and finding the correlation between EOY% and its components is the first priority [11][12][13]. Piccaglia and Marotti [14] reported that biomass weight and the number of umbels per plant are positively related to the essential oil content (R = 0.651 and 0.569, respectively) [14].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, direct selection on the basis of correlated response may not be fruitful [34]. For critical evaluation, the correlation coefficient needs to be split into direct and indirect effects using path coefficient analysis since, many characters affect a given trait [35]. Thus, the correlation and path coefficients in combination can give a better insight into cause-and-effect relationship between different pairs of characters [36].…”
Section: Path Coefficient Analysismentioning
confidence: 99%